2016
DOI: 10.1038/srep29358
|View full text |Cite
|
Sign up to set email alerts
|

Human induced pluripotent stem cell-derived hepatic cell lines as a new model for host interaction with hepatitis B virus

Abstract: Hepatitis B virus (HBV) is not eradicated by current antiviral therapies due to persistence of HBV covalently closed circular DNA (cccDNA) in host cells, and thus development of novel culture models for productive HBV infection is urgently needed, which will allow the study of HBV cccDNA eradication. To meet this need, we developed culture models of HBV infection using human induced pluripotent stem cell-derived hepatocyte lineages, including immature proliferating hepatic progenitor-like cell lines (iPS-HPCs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 32 publications
(44 reference statements)
1
49
0
Order By: Relevance
“…Previous studies including our data showed that iPS-Heps can respond to anti-viral IFN-a stimulation, which is susceptible to HBV [19,52,53]. Immature proliferating hepatic progenitor-like cell lines derived from iPS cells (iPS-HPCs) at a relatively immature stage of hepatic differentiation can be infected with HBV in vitro [19].…”
Section: Disease Models Of Hepatitis B Virusesmentioning
confidence: 74%
See 3 more Smart Citations
“…Previous studies including our data showed that iPS-Heps can respond to anti-viral IFN-a stimulation, which is susceptible to HBV [19,52,53]. Immature proliferating hepatic progenitor-like cell lines derived from iPS cells (iPS-HPCs) at a relatively immature stage of hepatic differentiation can be infected with HBV in vitro [19].…”
Section: Disease Models Of Hepatitis B Virusesmentioning
confidence: 74%
“…Hepatocyte-like cells derived from iPS cells (iPS-Heps) exhibit properties of hepatocytes, such as albumin secretion and metabolic functional properties. Several pathophysiological disorders can be reproduced using human iPS-Heps; on the contrary, the phenotypes of iPS-Heps are immature compared with adult mature hepatocytes with respect to albumin production, cytochrome P450 (CYP) activity and metabolic functions [18,19]. Recent reports have shown that patientderived iPS-Heps have been used to investigate the pathophysiology of genetic disorders, such as a1antitrypsin deficiency, glycogen storage disease type 1, Crigler-Najjar syndrome, hereditary tyrosinemia type 1, Gaucher disease, Niemann-Pick disease type C and Wilson's disease [14][15][16]20,21].…”
Section: Diseases Models Of Genetic Liver Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…Lentiviruses expressing shRNA were produced in 293T cells, as described. (26) HPPL (a mouse hepatoblast cell line) (27) or primary hepatoblasts were infected with the lentiviruses at five multiplicity-of-infection at day 3 of 2D preculture before cholangiocytic differentiation. Cells were collected on day 7 of preculture and subjected to 3D culture for cholangiocytic differentiation.…”
Section: Knockdown Assay Of Vip Receptors 1 Andmentioning
confidence: 99%